Introduction to financial technology - Freedman, Roy S. (Complete technology guides for financial services., 2006)
The financial technology environment is a dynamic, high-pressured, fast-paced world in which developing fast and efficient buy-and-sell order processing systems and order executing (clearing and settling) systems is of primary importance. The orders involved come from an ever-changing network of people (traders, brokers, market makers) and technology. To prepare people to succeed in this environment, seasoned financial technology veteran Roy Freedman presents both the technology and the finance side in this comprehensive overview of this dynamic area. He covers the broad range of topics invol.